Analisis Kinerja Penjualan UMKM Melalui Keunggulan Kompetitif Dalam Konteks Pengunaan Digitalisasi - Silaban, Pasaman; Silaban, Frederick Saroha; Steven, Orlando; Nababan, Youkki (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
The COVID-19 pandemic has had a major impact on many industries, including the economy. Indonesia's economic and business sectors have been hit hard by the Covid-19 outbreak. Many micro, small and medium enterprises (MSMEs) are confused because their companies are hindered and cannot even develop. The position of MSMEs is considered very significant because this sector is not only a source of livelihood, but also provides direct and indirect employment opportunities to people with relatively low levels of knowledge and skills. The purpose of this study is to measure and examine the variable ability of usage of e-commerce, usage of QRIS, in increasing competitive advantage and will ultimately improve the sales performance of MSME players in Medan city. This type of research is descriptive quantitative. This study aims to describe or describe the factors that influence Competitive Advantage such as Usage E-Commerce, Usage QRIS (mediating variable), and Sales Performance (mediator variable). The research location is in Medan City. The research time starts in April 2024 to July 2024. The number of samples or respondents in this study were 150 respondents. Data analysis to answer the hypothesis proposed using the Partial Least Square (PLS) method with the help of SmartPLS software version 3. The results concluded that based on the hypothesis of the direct effect of usage of QRIS, positively and significantly predicts competitive advantage with a value of 0.001 <0.005 and also Usage of QRIS positively and significantly predicts Sales Performances with a value of 0.000 <0.005.